Prevalence of overweight, obesity and altered abdominal circumference in school children aged 6 to 11 in Campo Grande/MS - Maria Isabel Carneiro Travi; Paulo Roberto Haidamus de Oliveira Bastos; Elenir Rose Jardim Cury Pontes (Universidade de Fortaleza, 2011)
Objectives: To estimate the prevalence of overweight, obesity and altered abdominal circumference in school children and analyze some factors associated with excess body weight. Methods: Children aged 6 to 11 years (n=728) from public and private schools of Campo Grande-MS, Brazil, joined in the study. The variables concerning the school childrenwere: identification data, breastfeeding, birth weight, feeding, practice of physical activities,body mass index (BMI) and abdominal circumference measurement; those concerning thefamily were the income per capita and the mothers' BMI and schooling. Results: The overallprevalence presented the following estimates: 478 (65.7%) eutrophic students, 119 (16.3%)overweight, 105 (14.4%) obese, and 26 (3.6%) underweight children. Altered abdominalcircumference was seen in 315 (43.3%) of the sample. The prevalence of overweight and obesity among school children showed a statistically significant difference according to thetype of school (p=0.018), body mass of mothers (p<0.001) and non-programmed physical activities (p<0.001). Conclusion: Altered abdominal circumference, seen in almost half ofthe samples of school children, may be an indicator of cardiovascular risk. Aspects like the attendance to private schools, overweight mothers and the absence of active leisure activitieswere associated with the overweight or obesity in school children.